2018
DOI: 10.1136/neurintsurg-2017-013481
|View full text |Cite
|
Sign up to set email alerts
|

In vitro measurement of the permeability of endovascular coils deployed in cerebral aneurysms

Abstract: A simple in vitro setup was developed to measure the permeabilities of coil masses based on traditional permeametry. Coil permeability should be considered when evaluating the hemodynamic efficacy of coiling instead of just packing density. Coils made of thicker wires may be more permeable, and thus less effective, than coils made from thinner wires. Whether aneurysm recurrence is affected by coil wire diameter or permeability needs to be confirmed with clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[9] A higher permeability of the PC400 has been described previously in an in vitro model of an 8 mm aneurysm when compared to other coils. [16] Only Kaesmacher et al reported an immediate 3A/3B mRROC in 29.7% of cases. [6] Nevertheless, at follow-up, we demonstrate that the proportion of a good obliteration rate increased significantly (24 out of 26 cases: 92%), especially in unruptured aneurysms (100% of the cases).…”
Section: Discussionmentioning
confidence: 96%
“…[9] A higher permeability of the PC400 has been described previously in an in vitro model of an 8 mm aneurysm when compared to other coils. [16] Only Kaesmacher et al reported an immediate 3A/3B mRROC in 29.7% of cases. [6] Nevertheless, at follow-up, we demonstrate that the proportion of a good obliteration rate increased significantly (24 out of 26 cases: 92%), especially in unruptured aneurysms (100% of the cases).…”
Section: Discussionmentioning
confidence: 96%
“…Being deployed into the IA sac, coils create a three-dimensional porous medium with varying pore sizes and shapes [19]. Because 3D coil configuration (and thus the pore spaces around the coils) cannot be obtained from imaging, we used 2 surrogate metrics defined in 2D to characterize and quantify coil distribution on the phantom cross-sections.…”
Section: Methodsmentioning
confidence: 99%